Animal Models, Therapeutics, and Vaccine Approaches to Emerging and Re-Emerging Flaviviruses - Thomas J. Baric; Z. Beau Reneer (Viruses)
Flaviviruses are arthropod-borne viruses primarily transmitted through the mosquito Aedes aegypti or Culex genus of mosquitos. These viruses are predominantly found in tropical and subtropical regions of the world with their geographical spread predicted to increase as global temperatures continue to rise. These viruses cause a variety of diseases in humans with the most prevalent being caused by dengue, resulting in hemorrhagic fever and associated sequala. Current approaches for therapeutic control of flavivirus infections are limited, and despite recent advances, there are no approved drugs. Vaccines, available for a few circulating flaviviruses, still have limited potential for controlling contemporary and future outbreaks. Mouse models provide us with a valuable tool to test the effectiveness of drugs and vaccines, yet for many flaviviruses, well-established mouse models are lacking. In this review, we highlight the current state of flavivirus vaccines and therapeutics, as well as our current understanding of mouse models for various flaviviruses.